Radiographic Healing and Functional Outcomes of Untreated Ulnar Styloid Fractures Following Volar Plate Fixation of Distal Radius Fractures: A Prospective Analysis. (May 2021) - Okoli, Michael; Silverman, Matthew; Abboudi, Jack; Jones, Christopher; Kirkpatrick, William; Liss, Frederic; Takei, T. Robert; Wang, Mark; Ilyas, Asif M.
Background: Ulnar styloid fractures (USFs) are common concomitant injuries associated with distal radius fractures (DRFs). Recent studies have found conflicting evidence on whether these fractures treated or untreated effect pain and functional outcomes. The purpose of this study was to prospectively evaluate pain and function outcomes of consecutively untreated USFs in surgically repaired DRFs. The study hypothesis was that there would be no difference in outcomes whether an USF is present or not, with all cases left untreated.Methods: A prospective study at a single institution of consecutive DRF treated surgically with volar locked plating was undertaken. No patients underwent fixation of an USF if present. There were no treated USF that were excluded. Patients with associated ulnar neck and shaft fractures were excluded. Functional outcome measures were analyzed using the Quick Disabilities of the Arm, Shoulder, and Hand score (QDASH) and the Patient-Rated Wrist Evaluation (PRWE) scores. Outcome measures were collected at 3 months and 1 year postoperatively.Results: There was an incidence of 52.2% (n = 70/134) USF associated with surgically treated DRF. By location, there were 52.9% (n = 37/70) ulnar styloid tip fractures and 46.1% (33/70) ulnar styloid base. There were 75.7% of USF (53/70) still not healed by 1-year follow-up. When comparing patients with a DRF without an USF versus DRF with an associated USF at 12 months, there was no statistical difference in the QDASH score (6.7 vs 8.4, P = .47) or the PRWE total score (4.8 vs 7.5, P = .24). Similarly, subgroup analysis showed no statistical difference in QDASH or PRWE scores at final follow-up in united USF versus nonunited USF subjects (QDASH 14.2 vs 6.8, P = .112; PRWE 14.8 vs 5.4, P = .185).Conclusions: USFs are a common concomitant injury occurring in nearly half of DRFs treated surgically. Our prospective cohort analysis showed that neither the presence, type, nor bony union status of a concomitant USF has any significant effect on patient outcomes or reoperations at 1-year postoperatively. Our study confirms our hypothesis that USF of the tip and base should be left untreated.